Association Between Blood Glucose Profiles with Severity of Covid-19 and Type 2 Diabetes Mellitus Patients - Ginting, Priska Krinanta; Santi Syafril (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Background: Individuals with diabetes mellitus (DM), hypertension, and severe obesity (BMI > 40 kg/m2) are more likely to be infected and are at a higher risk for complications and death from COVID-19. The purpose of the study was to evaluate association of Covid-19 severity with blood glucose profile in type 2 diabetes mellitus patients. Method: The study was conducted from June 2021 – September 2021 in the isolation inpatient room of RSUP. H. Adam Malik Medan, and the research samples were all newly patients diagnosed COVID-19 with T2DM comorbidity. The inclusion criteria were all patients aged ≥18 years, COVID-19 group:moderate, severe, and critical degrees, with comorbid T2DM. HOMA-IR was calculated based on fasting plasma insulin and fasting plasma glucose. Results:. There are significant differences in fasting insulin levels and insulin resistance (HOMA-IR) based on severity of Covid-19 infection. There are significant differences on fasting plasma insulin and HOMA-IR between medium degree vs critical degree, and severe degree vs critical degree (p < 0.01). Conclusion: There are significant association between Covid-19 severity with fasting insulin resistance (HOMA-IR) in type 2 Diabetes Mellitus patients, but there aren’t significant association between Covid-19 severity with fasting plasma glucose, post prandial glucose, or HbA1c.